Creating new opportunities for improving the quality of education through the promotion of private schools and especially their management - Сенчук, Оксана (Educological discourse, 2013)
The article indicates the importance of private education in Ukraine and new forms of school management. Private schools create favorable conditions for the active competition. It helps to improve the quality and the real right of parents to choose the educational institution in accordance with cultural and educational needs of the child.